Konsep Dasar External Causes Penyebab Luar Yang Tidak Spesifik - Aan Riski Susanto; Rosa Adelia Anhar; Liss Dyah Dewi Arini (Jurnal Mahasiswa Ilmu Kesehatan, 2024)
The basic concept of "external causes" or non-specific external causes refers to external factors that influence a phenomenon or event without pointing to a clear and defined cause. In various disciplines such as medicine, epidemiology, sociology, and economics, an understanding of non-specific external causes is essential to identify, analyze, and mitigate the impact of events that cannot be explained by internal or specific factors. These external causes can be the physical environment, socio-economic conditions, public policies, and unexpected natural events. This article aims to outline the basic concepts, analysis methodology, and implications of non-specific external causes in various study contexts. Through a deeper understanding of these external factors, it is hoped that more effective strategies can be obtained in managing risks and handling complex and multifaceted problems.